Mechanical behavior of concretes made with non-conventional organic origin calcareous aggregates. (10th August 2018) - Foti, D.; Cavallo, D.
Graphical abstract: Waste mussels' shells utilized as total or partial substitute of aggregate in concrete. The mussels' shells, consisting essentially of limestone, a material similar to that of the other components of concrete, well adapt to be added to a concrete mix as aggregate. The organic part on the shells has been totally removed with a cleaning process. Most important: Reduction of waste. The results showed: the shells of the mussels allow to obtain conglomerates having a good workability; even if no test has been carried out, the shells appear to have a good tensile strength; the compressive strength is reduced as the percentage of mussels' shells increases; the bending tests showed a higher peak for specimens with a higher percentage of mussels' flakes and a certain ductility of the behavior soon after the failure is reached; reduction of waste an improvement of the sustainability of the concrete. Highlights: Waste mussels' shells utilized as total/partial substitute of aggregate in concrete. Mussels' shells are good to be added to a concrete mix as aggregate. Compression and bending tests to analyze the behavior of this new concrete. Mussels' shells allow to obtain conglomerates having a good workability. Concrete samples with mussels' flakes showed a certain ductility of the behavior. Abstract: In this work the performance of plain concrete added with mussel shells of Mytilus galloprovincialis has been studied. In the Mediterranean Basin, this variety is among the most common wild and farming mussels. The type of mussel shell used comes from Italian shellfish farming, which generates 100, 000 tons per year of mussel shell waste. The mussel waste has been cleaned with bleach and using different abrasives, then boiled in water for 15 min and finally dried in order to ensure to eliminate all the organic parts. The natural gravel in the concrete mix has been replaced with different percentages of crushed shells. The results have been analyzed and discussed in order to evaluate the possibility to utilize this waste material for concretes improving the sustainability of the environment.